2013
DOI: 10.1002/dev.21188
|View full text |Cite
|
Sign up to set email alerts
|

Flexible memory retrieval in bilingual 6‐month‐old infants

Abstract: Memory flexibility is a hallmark of the human memory system. As indexed by generalization between perceptually dissimilar objects, memory flexibility develops gradually during infancy. A recent study has found a bilingual advantage in memory generalization at 18 months of age [Brito and Barr [2012] Developmental Science, 15, 812-816], and the present study examines when this advantage may first emerge. In the current study, bilingual 6-month-olds were more likely than monolinguals to generalize to a puppet tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 78 publications
7
76
0
Order By: Relevance
“…Evidence of similar inhibitory control outcomes have been reported for bilingual infants and toddlers as well (Kovács & Mehler, , ; Poulin‐Dubois et al., ). Recent work has also identified positive effects of bilingualism for other aspects of cognition, such as information encoding (Singh et al., ) and memory generalization (Brito & Barr, , ) for bilinguals as young as 6 months of age. The present study provides further evidence that early experience navigating bilingual environments influences how infants process perceptual input, and tunes learning mechanisms to meet the challenges of acquiring two languages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of similar inhibitory control outcomes have been reported for bilingual infants and toddlers as well (Kovács & Mehler, , ; Poulin‐Dubois et al., ). Recent work has also identified positive effects of bilingualism for other aspects of cognition, such as information encoding (Singh et al., ) and memory generalization (Brito & Barr, , ) for bilinguals as young as 6 months of age. The present study provides further evidence that early experience navigating bilingual environments influences how infants process perceptual input, and tunes learning mechanisms to meet the challenges of acquiring two languages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a nascent literature examining bilingual cognitive development in infancy suggests that bilinguals may differ from monolingual infants in some aspects of information processing. This research has revealed that bilingual experience is associated with positive outcomes for inhibitory control (Kovács & Mehler, , ; Poulin‐Dubois, Blaye, Coutya, & Bialystok, ), information encoding (Singh et al., ), and memory generalization (Brito & Barr, , ). For example, Kovács and Mehler () found that 7‐month‐old infants from bilingual homes were more effective than monolinguals at inhibiting a previously learned response to visual stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study with 6-month-old bilingual and monolingual infants (Brito & Barr, 2014), bilinguals were able to imitate the behavior (i.e., demonstrate memory generalization) in a difficult task, where the target object changed in two features (color and shape), and in an easy task, where the target object changed in only one feature (color), while monolinguals were only able to imitate in the easy task. In another study, with older participants (18-month-olds) performing a more difficult generalization task, bilinguals demonstrated successful deferred imitation performance, whereas monolinguals did not (Brito & Barr, 2012).…”
Section: Too Much Of a Good Thing: Trilingualism Decreases The Bilmentioning
confidence: 99%
“…The bilinguals outperformed the monolinguals on the Shape Stroop task, a conflict task in which children need to selectively attend to a target stimulus while ignoring a non-target stimulus, but comparable between-group performance was observed on the delay tasks. There is even some evidence of executive function benefits during infancy on tasks measuring inhibitory control (Kovacs & Mehler, 2009) and memory generalization (Brito & Barr, 2012, 2014; Brito, Grenell, & Barr, 2014). …”
Section: Introductionmentioning
confidence: 99%